Dysfunctions in communication in business organizations in Southern Poland = Dysfunkcje w komunikacji w organizacjach gospodarczych Polski Południowej - Makowiec, Marek; Potocki, Arkadiusz (Zielona Góra: Faculty of Economics and Management Press)
In the study authors, on the basis of completed two different tests, pointed out the most common difficulties and dysfunctions in communication in contemporary organizations. Both traditionally functioning economic entities and organizations which employ teleworkers, where there is much more variety of problems, including due to lack of physical contact between people, were analyzed. In such situations a big impact on improving the process of information flow between people has modern technology and IT technology, which, however, has a negative impact on humans.
Keywords: komunikacja; komunikowanie się w organizacjach; informacja; dysfunkcje w odbiorze informacji; utrudnienia w procesie przesyłania informacji; communication; communication in organizations; information; dysfunctions in process of receiving information; difficulties in the process of sending information; process receiving information